2021
DOI: 10.1332/030557320x15987279194319
|View full text |Cite
|
Sign up to set email alerts
|

Beyond nudge: advancing the state-of-the-art of behavioural public policy and administration

Abstract: This Themed Issue features theoretical, methodological, and empirical advancements of the state-of-the-art in behavioural public policy and administration. In this introduction, we develop a behaviourally-informed, integrated conceptual model of the policy process that embeds individual attitudes and behaviour into context at the meso and macro level. We argue that behavioural approaches can be situated within a broader tradition of methodological individualism. Despite focusing on the micro level of policy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…For example, recent work in behavioral governance analyzing citizens' perceptions of policy nudges regarding health, the environment, and public safety showed that trust in public institutions increased when 'citizens are invited to participate, to make active choices, and to give feedback to planned interventions' (Sunstein et al, 2019(Sunstein et al, , p. 1437. Thus, our work may contribute to behavioral public administration (Battaglio et al, 2019;Grimmelikhuijsen et al, 2017; and behavioral public policy (Ewert et al, 2020;Oliver, 2015Oliver, , 2017Sanders et al, 2018) by suggesting the presence of a pro-public sector bias when normative outcomes are considered.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, recent work in behavioral governance analyzing citizens' perceptions of policy nudges regarding health, the environment, and public safety showed that trust in public institutions increased when 'citizens are invited to participate, to make active choices, and to give feedback to planned interventions' (Sunstein et al, 2019(Sunstein et al, , p. 1437. Thus, our work may contribute to behavioral public administration (Battaglio et al, 2019;Grimmelikhuijsen et al, 2017; and behavioral public policy (Ewert et al, 2020;Oliver, 2015Oliver, , 2017Sanders et al, 2018) by suggesting the presence of a pro-public sector bias when normative outcomes are considered.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 85%
“…In conclusion, being set during a global pandemic that requires a comparative and multi-level governance response, our work may help the integration and cross-fertilization of behavioral insights (Battaglio et al, 2019;Ewert et al, 2020;Grimmelikhuijsen et al, 2017;Oliver, 2015Oliver, , 2017 into mainstream public policy scholarship. Sector type and duration of use are important considerations in assessing citizens' readiness to grant access to personal information, especially given the global efforts to employ private sector research and development to combat an unprecedented public health emergency (e.g., Mazzucato & Kattel, 2020).…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 93%
See 1 more Smart Citation
“…What modern managers may now acutely need to be trained for is the shift from (moral) values to preferences, both for individuals and communities, with the aim to facilitate behavioural change and long-term commitment, trust, social acceptance and buy-in of the notion of sustainability and its implications to all aspects of corporate activities, through effective strategies that shall go beyond nudging. This is stated in [20] where it is confirmed the non-lasting nature of nudging which we aim to overcome by means of educating the managers in a hands-on way.…”
mentioning
confidence: 80%
“…policy researchers (Richard Thaler, Esther Duflo, Abhijit Banerjee & Michael Kremer). Although a 'behavioural turn' inspired by behavioural economics and psychology has been observed both in public policy and in public administration, the subfields of 'behavioural public policy' (BPP) and 'behavioural public administration' (BPA) rarely speak directly to each other (Ewert et al, 2021) and remain somewhat separated from more mainstream approaches to public policy. In this introduction and across the Special Issue we seek to remedy this, drawing together concepts from BPP and BPA to develop the concept of 'behavioural governance'.…”
mentioning
confidence: 99%